PENGARUH LIABILITAS, ROE, DAN BOPO TERHADAP PROFITABILITAS FINTECH DI INDONESIA - Afifah Bety Ariani; Atika Fatimah (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The aim of this research is to determine the influence of Liabilites, ROE, and BOPO on Fintech Profitability in Indonesia. The method used in this research is multiple linear regression analysis. Based on the research results, liabilities have no effect on net profit after tax. This is because if economic conditions are bad, debt can reduce company profits. However, if the economy is normal, debt can increase profitability. ROE affects net profit after tax, because the use of owner’s capital through company management works efficiently to increase company profits. This will create a good return for the business because the capital owner receives a profit. As the company’s income increases, the return on equity will of course be higher, which is useful for other working capital used to support the company’s operations. BOPO affects net profit after tax because the lower the BOPO value, the more efficient the fintech is in managing